Violence in the ancient and medieval worlds (Leuven ; Paris ; Bristol, CT)
x, 582 sayfa
Keywords: “Being an integral element of how humans interact with one another, violence, however disruptive, often also manifests itself as an ordering force. In this collection of essays, the contributing authors explore this particular aspect of violence from a wide variety of perspectives, in a set of studies that focus on both the ancient and medieval worlds. Case-studies in the section on Antiquity include work on such issues as domestic violence; violence and myth; violence in Greek and Roman historiography, poetry, comedy and tragedy, and art; women and violence; violence and pollution; and various studies on classical Greek and Roman perceptions of violence. The medieval section continues with papers that look into the role of violence in the saints' lives and passions, violence in the love poems of the Carmina Burana, as well as several studies that center on actual cases of violence, such as violence and women in medieval Galicia and violence at Portuguese universities during the High Middle Ages. This book is essential reading for everyone interested in how and why violence came to be embedded in the cultural practices of classical Greece, ancient Rome, and medieval Europe.” --